Prevailing traditional health care services in Western Ladakh, Indian Trans-Himalaya - Angmo, Kunzes; Gailson, Lotos; Adhikari, Bhupendra; Rawat, Gopal; Bhat, Jahangeer; Bussmann, Rainer W; Malik, Zubair A. (Ethnobotany Research and Applications, 2022)
Background: There has been a spurt in revival of Traditional Health Care Services (THCS) in different parts of the world due to increasing awareness about their importance and the initiatives taken by the local governments. Ladakh, located in the Indian Trans-Himalaya represents an ethno-cultural landscape with well-established history of use of traditional medicines in healing of different ailments. However, several THCS so far remained informal and have not been documented properly. The present study aimed to assess and document the status of three different THCS viz., Amchis, Akhons and Shamans in western Ladakh. Methods: Both qualitative and quantitative data about the 36 Amchis, 53 Akhons and 21 Shamans was collected through questionnaire surveys, semi-structured interviews and participatory appraisals in three valleys of western Ladakh were organized. Results: The Amchis and Akhons were mostly middle aged and older men while Shamans were mostly young women. All the three healers were generally illiterate with weak socio-economic status. Amchis and Akhons were more experienced as it was their main profession and received the knowledge hereditary. Amchis and Shamans were mostly Buddhist while Akhons were Muslim. These traditional healers treated 17 different ailments. Conclusion: The local population of the western Ladakh reported that most of the sub-centers and primary health centers lack medical equipment, drugs, and skilled workforce. Due to deficiencies in health care services the use of indigenous healthcare practices is common. Efforts should be made to fortify THCS by collaborating with modern medicine systems to improved local health care. Of all the THCS, the Amchi system or Sowa-rigpa seems to be the most codified and might therefore be the most logical one to be integrated into the public health care system. Keywords: Traditional health care system, Amchi, Akhon, Shaman, Western Ladakh